Elite tennis player's perceptions of coaching effectiveness - Zhu, Q.; Bloom, G. A.; Xu, C.; Alexander-Urquhart, D.; Guo, L.; Zhu, Y. (International Journal of Sports Science & Coaching, 2024)
The purpose of this study was to explore the experiences of six elite Chinese tennis players and their perspectives of coaching effectiveness within their sport. We collected data using two approaches: semi-structured interviews and player documents (e.g., detailed biographies, competition experience, and performance statistics). Data were analyzed using a reflexive thematic analysis to identify the coaches` knowledge and behaviors that elite Chinese players considered to be effective and ineffective within the training and competitive landscape. We constructed two overarching themes to represent elite tennis player's perceptions regarding coaching effectiveness: (1) perceived coaching roles (i.e., the coach as a planner, teacher, and strategist), and (2) coaching as a social phenomenon (i.e., interpersonal styles and networks, effective and ineffective behaviors). Theoretically, this study aligns with the 3 + 1Cs model of the coach-athlete relationship and enriches the literature on coaching effectiveness in elite tennis. Practically, this study underscores the value of coaching knowledge and behaviors in shaping player's competitive performance and sociopsychological abilities and identifies recommendations for coaches and players to develop harmonious and meaningful relationships within the elite tennis context.